2022
DOI: 10.1186/s12879-022-07269-7
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of Veterans attitudes and willingness to receiving the COVID-19 vaccine: a mixed methods study

Abstract: Background While several safe and effective COVID-19 vaccines have been available since December 2020, many eligible individuals choose to remain unvaccinated. This vaccine hesitancy is an important factor affecting our ability to combat the COVID-19 pandemic. Methods The objective of the study was to examine the attitudes and willingness among US Veterans toward receiving COVID-19 vaccination. The study used a quantitative qualitative mixed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Using data from the UK, Freeman et al and Veli et al found that the exposure to information about vaccine efficacy reduces vaccine hesitancy [18,19]. Denford et al from interviews in the UK and Gardner et al from the US found that vaccine hesitancy was associated with lower trust in the government [20,21]. By Southeast Asian data, Duong and Antriyandarti also found that respondents who were more informed about efficacy were less vaccinehesitant [22].…”
Section: Our Aimmentioning
confidence: 99%
“…Using data from the UK, Freeman et al and Veli et al found that the exposure to information about vaccine efficacy reduces vaccine hesitancy [18,19]. Denford et al from interviews in the UK and Gardner et al from the US found that vaccine hesitancy was associated with lower trust in the government [20,21]. By Southeast Asian data, Duong and Antriyandarti also found that respondents who were more informed about efficacy were less vaccinehesitant [22].…”
Section: Our Aimmentioning
confidence: 99%
“…Using Southeast Asian data, Duong and Antriyandarti found that respondents who were more informed about vaccine efficacy were less vaccine hesitant [ 32 ]. Denford et al found from interviews in the UK and Gardner et al found from a survey in the US that vaccine hesitancy was associated with lower trust in the government [ 33 , 34 ]. Using extensive panel data from 12 countries, Algan et al found that confidence in science is significantly associated with attitudes toward vaccinations [ 35 ].…”
Section: Our Aimmentioning
confidence: 99%
“…The mistrust of military-connected populations was again highlighted throughout the COVID-19 pandemic when mistrust was prevalent among the broader American population (Gardner et al, 2022). In a 2022 survey of Veterans, almost 40% of participants stated that they would not receive the COVID-19 vaccine (Gardner et al, 2022).…”
Section: Mistrust and Specific Populationsmentioning
confidence: 99%
“…Trust is an important part of the patient experience and patient-provider relationship; it is because of trust in the collective health care professions that patients seek care from these experts during their most vulnerable moments (e.g., Eagan, 2019). However, there has been a trust crisis in the United Statesone that came into clear focus during the COVID-19 pandemic, when many Americans expressed distrust in government, science, health care providers, news media, and even in facts or truth (e.g., Gardner et al, 2022). According to a recent poll, fewer than one in three Americans think that government officials are credible, and the majority of Americans find it difficult to assess what is real versus fake news (Edelman Intelligence, 2018).…”
Section: Introductionmentioning
confidence: 99%